Genetic variability and association study of SSR markers for yield and powdery mildew disease in pea (Pisum sativum) - REGINAH, PHEIRIM; SINGH, KONJENGBAM NOREN; RAJESH, T; MAYURAKSHEE, MAHANTA; S, SAMUTHIRAPANDI; LYNGDOH, ANDREAN ALLWIN; CHAMROY, THEMMEICHON (The Indian Journal of Agricultural Sciences, 2024)
Makhyatmubi, one of the most popular local varieties of field pea (Pisum sativum L.) in Manipur has morpho- physiological bottlenecks such as tall nature and high susceptibility to fungus Erysiphe pisi causing powdery mildew disease. Therefore, an experiment was conducted during winter (rabi) seasons of 2018–19 and 2020–21 at College of Post-Graduate Studies in Agricultural Sciences (Central Agricultural University, Imphal, Manipur), Umiam, Meghalaya to generate genetic variability by hybridization of Makhyatmubi with Prakash variety which is a well-known powdery mildew resistant variety in India and possesses several contrasting characters. Fruitful heterosis was estimated with highest record in number of pods per plant (114.75%) and seed yield per plant (108.04%). These two characters also showed high PCV, GCV, heritability and GAM. Number of pods per plant (0.95) was found to have highest positive significant correlation with seed yield per plant. MP-5 and MP-119 recorded superior performance in several characters under study. For the association study of simple sequence repeats (SSR) markers, easily scorable polymorphic markers were selected for surveying association with the traits. Results revealed that SSR marker AA122 may be associated with seed yield and number of pods per plant while marker AA136 with number of seeds per pod. A5 marker was found to be associated with the powdery mildew disease. Hence, it can be employed for marker assisted selection (MAS) to identify and select pea genotypes exhibit resistance to powdery mildew disease.